1999
DOI: 10.1093/hmg/8.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ATM gene mutations in 66 ataxia telangiectasia families

Abstract: Ataxia telangiectasia (AT) is an autosomal recessive disease characterized by neurological and immunological symptoms, radiosensitivity and cancer predisposition. The gene mutated in AT, designated the ATM gene, encodes a large protein kinase with a PI-3 kinase-related domain. In this study, we investigated the mutational spectrum of the ATM gene in a cohort of AT patients living in Germany. We amplified and sequenced all 66 exons and the flanking untranslated regions from genomic DNA of 66 unrelated AT patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
148
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(163 citation statements)
references
References 49 publications
14
148
1
Order By: Relevance
“…The frequencies of the variant alleles 5557A, 5558T and 3161G are in good agreement with previous studies in the Caucasian population (Dork et al, 2001;Spurdle et al, 2002;Mauget-Faysse et al, 2003). The frequency of the intronic SNPs ivs38-15g4c (Thorstenson et al, 2001) and ivs38-8t4c (Sandoval et al, 1999) have previously only been determined in a small number of individuals. The ivs38-15 is the rarer of the two variants, the c allele being present at an allele frequency of 0.004, while the ivs38-8c allele is found at a frequency of 0.036.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The frequencies of the variant alleles 5557A, 5558T and 3161G are in good agreement with previous studies in the Caucasian population (Dork et al, 2001;Spurdle et al, 2002;Mauget-Faysse et al, 2003). The frequency of the intronic SNPs ivs38-15g4c (Thorstenson et al, 2001) and ivs38-8t4c (Sandoval et al, 1999) have previously only been determined in a small number of individuals. The ivs38-15 is the rarer of the two variants, the c allele being present at an allele frequency of 0.004, while the ivs38-8c allele is found at a frequency of 0.036.…”
Section: Resultssupporting
confidence: 91%
“…Strong linkage disequilibrium has been found between 3161G (P1054R) and the variant allele at 2572C (F858L). It has also been found to occur in cis to the splicing mutation 3576G to A found in some AT patients of South or South East European descent (Sandoval et al, 1999) although this splicing mutation was neither present in the patient HA220 nor in any other breast cancer patient carrying the 3161G allele (Dork et al, 2001). There may, however, be other variants on this haplotype (including noncoding alterations) that have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies, 19,[28][29][30][31][32] we showed a decreased ATM protein in 14 of the 16 A-T confirmed cell lines. Recent studies based on transfection of ATM constructs carrying various missense mutations showed that some missense mutations were associated with decreased ATM protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…16 The PCR products were sequenced whenever variant chromatogram patterns were detected. 3,4 Sequence changes were compared to published results 17,18 and ATM databases (http://chromium.liacs.nl/LOVD2/home.php). To exclude consideration of rare polymorphisms, sequence changes were classified as pathogenic mutations only if they were previously reported as causative mutations in AT patients or were predicted to cause protein truncation.…”
Section: Mutational Analysis Of the Atm Genementioning
confidence: 99%